2009
DOI: 10.1182/blood-2008-11-190330
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum at GATA1 provides insights into mutagenesis and leukemogenesis in Down syndrome

Abstract: Down syndrome (DS) children have a unique genetic susceptibility to develop leukemia, in particular, acute megakaryocytic leukemia (AMkL) associated with somatic GATA1 mutations. The study of this genetic susceptibility with the use of DS as a model of leukemogenesis has broad applicability to the understanding of leukemia in children overall. On the basis of the role of GATA1 mutations in DS AMkL, we analyzed the mutational spectrum of GATA1 mutations to begin elucidating possible mechanisms by which these se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 54 publications
2
61
0
1
Order By: Relevance
“…These data are consistent with the frequencies of 78% by Alford et al (2011), 74% by Cabelof et al (2009), 83% by Hitzler et al (2003) and 100% by Wechsler et al (2002).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These data are consistent with the frequencies of 78% by Alford et al (2011), 74% by Cabelof et al (2009), 83% by Hitzler et al (2003) and 100% by Wechsler et al (2002).…”
Section: Discussionsupporting
confidence: 81%
“…Acquired mutations in exon 2 of the hematopoietic transcription factor GATA1 mapped at Xp11.23 are consistently present in the affected cells of children with TMD and ML-DS, leading to expression of N-terminally truncated GATA1s protein (Wechsler et al, 2002;Cabelof et al, 2009). These GATA1 alterations are somatic and are therefore no longer detectable in remission samples (Ahmed et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosome 21-localized genes, including cystathionine-β-synthase (CBS) and zinc-copper superoxide dismutase (SOD1), are linked to abnormal intracellular folate metabolism, uracil accumulation and increased oxidative stress leading to DNA damage. 13 Past studies have demonstrated that the high event-free survival rates of Down syndrome patients with AMkL are related to increased in vitro sensitivity of Down syndrome megakaryoblasts to cytarabine (ara-C) and daunorubicin, 14 due in part to the presence of GATA1 mutations. The relationship between GATA1 mutations and outcome is highlighted by the lower frequency of GATA1 mutations in Down syndrome AML patients greater than 4 years of age, who have significantly lower event-free survival (<35%) and increased relapse rates compared to the majority of Down syndrome AML patients.…”
mentioning
confidence: 99%
“…İkinci tetiği çeken faktörler ise hala tanım-lanabilmiş değildir (5,6). Klinik olarak GMPH gelişmesi durumunda GATA-1 mutasyon analizi yapma imkanı varsa tanı koydurucudur (5,6,(10)(11)(12)(13)(14). Biz GATA-1 mutasyonuna bakma imkanı-mız olmadığından bakamadık.…”
Section: Olgu Sunumuunclassified